Controlled Growth of Patterned Conducting Polymer Microsuckers on Superhydrophobic Micropillar‐Structured Templates. (24th May 2018) - Chen, Yupeng; Meng, Jingxin; Zhu, Zhongpeng; Zhang, Feilong; Wang, Luying; Gu, Zhen; Jiang, Lei; Wang, Shutao
Abstract: Morphology greatly impacts the performance improvement of conducting polymers for signal detection, actuator microfabrication, and droplet manipulation applications. However, most of the previous methods cannot satisfy practical demands due to their intrinsic drawbacks. Here, a general strategy is developed for the fabrication of patterned conducting polymers with precisely controlled microstructures (e.g., polypyrrole microsuckers) by regulating the solid/liquid/gas triphase interface and electrochemical polymerization. By regulating the distance between the Pt plate and micropillar‐structured templates, the growth directions of the microsuckers on the pillar tops change from upward (+26 ± 5°) to downward (−32 ± 7°), and their positions to the pillar tops are changed from proximal to distal due to an adjustment in the solid/liquid/gas triphase interface. The influencing factors on the microsucker growth performance, such as the time and current of electrochemical polymerization, the shape and size of micropillars, the type of conducting polymers, are systematically investigated. Furthermore, the as‐prepared microsuckers can be used for transporting water droplets because of their adjustable adhesion to water, which linearly increased from 33.5 ± 2.3 to 61.1 ± 1.2 µN with an increase in the projected epitaxial length of the microsuckers from 3.38 ± 0.39 to 8.78 ± 0.79 µm. Abstract : Conducting polymer microsuckers with controlled growth directions and positions are patterned on micropillars by the combination of solid/liquid/gas triphase interface regulation and electrochemical polymerization. The influencing factors on the growth of microsuckers are systematically investigated. Furthermore, the as‐prepared microsuckers can be used to transport water droplets because of their adjustable adhesion to water.